2017
DOI: 10.1016/j.tra.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and prospects of applying asset management principles to highway maintenance: A case study of the UK

Abstract: Past models and tools that support in the decision making process based on Asset Management Principles (AMP) are lacking in terms of the effective outcomes and transparency of the process in the highway maintenance. There is also little research on how to align the decision areas when applying AMP and how to improve the inclusive effectiveness. Hence, the paper focuses on examining the challenges and prospects of applying AMP in a highway maintenance agency or department. An exploratory research method was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Similarly, in their review of statistical models for remaining lifetime estimation, Si et al (2011) concluded that many quantitative attempts fail because of the lack of quality and availability of data, and hence argue that methods based on the knowledge of experts may be a solution. Similar findings are reported by Garg and Deshmukh (2006), Lin et al (2006), Mathew and Hargreaves (2008), Jongen (2012), Kerkhof et al (2014) and Shah (2017), just to mention a few. A different aspect of the availability of data is captured by Ding and Kamarudin, who argued that not every condition can be translated into algebraic form and replicated accurately.…”
Section: A Review Of Asset Management Literature and Practicesupporting
confidence: 85%
See 2 more Smart Citations
“…Similarly, in their review of statistical models for remaining lifetime estimation, Si et al (2011) concluded that many quantitative attempts fail because of the lack of quality and availability of data, and hence argue that methods based on the knowledge of experts may be a solution. Similar findings are reported by Garg and Deshmukh (2006), Lin et al (2006), Mathew and Hargreaves (2008), Jongen (2012), Kerkhof et al (2014) and Shah (2017), just to mention a few. A different aspect of the availability of data is captured by Ding and Kamarudin, who argued that not every condition can be translated into algebraic form and replicated accurately.…”
Section: A Review Of Asset Management Literature and Practicesupporting
confidence: 85%
“…However, research indicates that the knowledge of operators and technicians is not always used to its full potential (Xerri et al, 2015), which is nicely shown in this quote: "[i]t appears through the interviews that the organisations continue to see the operators and technicians as skilled hands, rather than also having brains and being very sophisticated sensors" (Lin et al, 2007, p. 123). However, it is this knowledge and experience that is necessary to gain the 'bigger operational picture' (Shah et al, 2017) that is important in Asset Management.…”
Section: Alcm Is a Multidisciplinary Practicementioning
confidence: 99%
See 1 more Smart Citation
“…While some research has been focused on interoperability within the design and construction phase (Amann, 2015;Kivits, 2013) there is less focus on interoperability between construction and operationto underpin tasks such as Asset Management. Asset Management provides information regarding the value of an asset (Shah, 2017), while the increasingly stricter criteria in infrastructure regarding safety and efficiency under the pressure of constantly lowering the construction cost, has highlighted its implementation as a tool to obtain better results by utilizing fewer resources (Moon et al, 2009).…”
Section: Motivationmentioning
confidence: 99%
“…The importance of having a data inventory of a project's assets (Shah, 2017) enables the implementation of asset management systems in IFC. The extensive utilization of BIM and 3D Modelling in the built environment enables the extension of IFC not only in infrastructure but also to incorporate information that are valuable in asset management.…”
Section: Ifc and Asset Managementmentioning
confidence: 99%